Systematic Evaluation and Screening of Clinical Efficacy of Anal Fistula based on Randomized Controlled Trial - Zhang, Wei; Feng, Wenzhe (Journal of Contemporary Medical Practice, 2025)
Objective: To systematically evaluate the clinical efficacy of wound healing after anal fistula, screen the basic drugs, and provide evidence-based medical evidence for clinical drugs. Methods: A systematic literature search of 7 domestic and foreign databases included a randomized controlled trial (RCT) for the treatment of anal fistula, data extraction and bias assessment by two reviewers. The Cochrane risk of bias assessment tool and StataSE 15.0 software were used for quality evaluation and meta-analysis. We used the Apriori algorithm in SPSS statistics22.0 software to analyze the associations between the drugs and select the basic drugs of TCM for restoring wound healing. Results: 32 randomized controlled studies were included in 3445 patients. The results of Meta-analysis showed that, compared with the conventional postoperative wound dressing change, external treatment of TCM could effectively improve the cure rate [RR= 0.77,95%CI (0.71,0.82), P < 0.001]., Effectively shorten the wound healing time: [WMD = 6.00, 95%CI(4.58, 7.42), P< 0.001], Effective pain relief: [WMD = 0.95, 95%CI(0.51, 1.38), P< 0.001], Reduce wound exudation: [WMD = 0.49, 95%CI(0.41, 0.57), P< 0.001], Reduction of wound oedema degree [WMD = 0.43, 95%CI(0.28, 0.58), P< 0.001]. All of the differences were statistically significant. The data mining results showed that the association rules showed that the drug combination of drug-drug-drug-free and corner-drug-angelica had high support and confidence, and the cluster analysis obtained four types of prescriptions, which were the basic drugs for the treatment of anal fistula. Conclusion: External treatment of Chinese medicine greatly alleviates the pain and edema of anal fistula, significantly shortens the healing time of the wound, and the clinical cure rate is obviously better than that of conventional dressing change. This treatment is relatively safe and helps patients to recover as soon as possible to shorten the length of hospital stay.